How does Resilience Predict Cognitive Rumination in College Students? - Mulawarman, Mulawarman; Rindi Antika, Eni; Afriwilda, Mayang T.; Prabawa, Abi Fa'izzarahman; Nadhita, Galuh; Purboaji, Nawang (Universitas Negeri Padang, 2023)
Resilience is important for students to rise from stressful events such as cognitive rumination. Cognitive rumination makes students trapped in contemplation about their problems, resulting in students becoming unproductive. Therefore, this study aims to see the effect of resilience on cognitive rumination of Faculty of Education and Psychology Universitas Negeri Semarang and Faculty of Teaching and Education Universitas Bengkulu students. Quantitative methods were used in this study with an ex-post facto design. The population in this study is FEP UNNES and FETT UNIB students. A total of 320 FEP UNNES students and 292 FETT UNIB students were used as samples with purposive random sampling techniques. The data collection technique used a psychological scale of resilience (24 items) and a psychological scale of cognitive rumination (27 items). Hypotheses are tested and analyzed using simple regression analysis techniques. The results of this study showed that resilience had a significant negative effect on students' cognitive rumination (R=.890, R2=.793, β=-.890, t=112.605, and p<0.001). These results mean that resilience contributes 79,3% to cognitive rumination, so students who have high resilience are not easy to get caught up in negative rumination and remain productive in carrying out their academic activities. Further implications of this research for the field of guidance and counseling studies in higher education are to provide an initial foundation for digging deeper into aspects that can increase resilience in college students through experimental research. Researchers recommend looking at other perspectives of the subjects studied. For example, by adding a gender moderator variable to see differences in levels of resilience between male and female. In addition, expanding the range of research subjects to a wider range will further increase the generalizability of research with different sampling techniques.